Designing ferrierite-based catalysts with improved properties for skeletal isomerization of n-butene to isobutene. Issue 50 (20th June 2017) - Hu, Haiqiang; Ke, Ming; Zhang, Ka; Liu, Qiang; Yu, Pei; Liu, Yang; Li, Changchun; Liu, Wen
Abstract : The crystal morphology and size of ferrierite catalysts were controlled by a suite of crystallization methods and structure-directing agents. Abstract : The crystal morphology and size of ferrierite catalysts were controlled by a suite of crystallization methods and structure-directing agents. In particular, nano-sized ferrierite could be obtained by using tetramethylammonium hydroxide and pyrrolidine as double structure-directing agents under dynamic crystallization. The catalysts were analysed by XRD, SEM, N2 adsorption–desorption, NMR, XRF, NH3 -TPD, Py-IR, and TGA, and the characteristics were correlated with their catalytic performance in the skeletal isomerization of n -butene. The results clearly indicated that all the catalysts have a similar crystallinity, Si/Al ratio, and total number of acid sites, while a decrease in their crystal size leads to more pore mouth acid sites. The nano-sized ferrierite showed better stability and higher activity, which were related to their crystal morphology, size, and pore mouth acid. In addition, we further confirmed that high isobutene selectivity can be produced by monomolecular reaction.